2013
DOI: 10.1080/09243046.2013.768324
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior and lifetime distribution of impact-damaged carbon fiber/toughened epoxy composites under compressive loading

Abstract: This paper presents fatigue lifetime data of impact-damaged carbon fiber/toughened epoxy composites under compressive loading to elucidate the lifetime prediction methodology based on statistical approaches. Drop-weight impact damage was induced to a composite specimen with impact energy of 6.7 J/mm in accordance with ASTM D7136. Postimpact fatigue tests were conducted using a test fixture defined in ASTM D7137 under compression-compression loading (R = 10) at room temperature. The maximum compressive stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Comparing post impact damaged composites under tension-compression (T-C) and compression-compression (C-C) fatigue, Mitrovic and co-workers reported almost no difference in T-C damage mode between the undamaged and impact-damaged composites, whereas C-C fatigue of impact-damaged composites at high stress levels (70-80%) revealed extensive damage evolution [111]. Melin and Schon [112] further stipulated the post-impact crack line follows the buckle in the CFRP material during compressive fatigue, while Ogasawara and co-workers [113] (using high strength T800S/3900-2B epoxy matrix CFRP) reported that in thick (32 ply) quasi-isotropic laminates [+45, 0, −45, +90, 0, 0] 4s , that post-impact compressive fatigue advances damage, but primarily within the boundaries of the impact-damaged region.…”
Section: Effect Of Pre-existing Damage On the Fatigue Propertiesmentioning
confidence: 99%
“…Comparing post impact damaged composites under tension-compression (T-C) and compression-compression (C-C) fatigue, Mitrovic and co-workers reported almost no difference in T-C damage mode between the undamaged and impact-damaged composites, whereas C-C fatigue of impact-damaged composites at high stress levels (70-80%) revealed extensive damage evolution [111]. Melin and Schon [112] further stipulated the post-impact crack line follows the buckle in the CFRP material during compressive fatigue, while Ogasawara and co-workers [113] (using high strength T800S/3900-2B epoxy matrix CFRP) reported that in thick (32 ply) quasi-isotropic laminates [+45, 0, −45, +90, 0, 0] 4s , that post-impact compressive fatigue advances damage, but primarily within the boundaries of the impact-damaged region.…”
Section: Effect Of Pre-existing Damage On the Fatigue Propertiesmentioning
confidence: 99%
“…Subsurface delaminations, along with flaws present from fabrication, may also grow over the lifetime of the part due to normal loads. [7][8][9] In this paper, we propose a process to utilize significantly more of the information available about a part over its lifetime in order to better estimate the state of the part. We propose a method where the lifetime flash thermography data is used in a Bayesian filter to track the damage state of a part.…”
Section: Introductionmentioning
confidence: 99%
“…These materials, which are fabricated from layers of fiber in a cured matrix, may sustain damage that cannot be identified from surface inspection. Subsurface delaminations (areas where the layers of the composite have disbonded), along with flaws present from fabrication, may grow, due to normal loads, over the lifetime of the part [2]. Subsurface delaminations caused by impacts can result in a significant loss of load carrying capacity but leave little to no indication of damage on the surface at the point of impact or surrounding areas.…”
Section: Introductionmentioning
confidence: 99%